Posted by **Blaire** on Sunday, March 2, 2014 at 6:29pm.

Prove: [(tan^2theta+1)(cos^2theta-1)]=1-sec^2theta

## Answer this Question

## Related Questions

- Math - sin theta = 8/17 and theta is in the second quadrant. Find sin(2theta),...
- Precalc+trig - Solve tan(40/90) for the double angle cos(2theta). I know I use ...
- Math - sin theta = 8/17 and theta is in the second quadrant. Find sin(2theta),...
- Math - 1)Find cos theta if sin theta=3/5 and 90 degrees<theta<180 degrees...
- math - There are no typos and no work b/c I don't know how to do them. Thanks. 1...
- Calculus - What is the integral of 1-tan^2theta from 0 to pi/3? Using the ...
- Math - There are no typos and no work b/c I don't know how to do them. Thanks. 1...
- trig - tan^2theta+6=sec^2theta+5
- maths - if cot theta =7/8 , evaluate (1+sin^2theta)(1-sin^2theta)/(1+cost^2theta...
- Prove or Disprove - Cos(X+y)cos(x-y)= cos^2theta - sin^2theta I foiled the left ...